Climate Change in Indigenous Peoples' Narratives: A Case of Doma People of the Zambezi Valley - Mhondera, Achieford; Mukaro, Laston; Mabugu, Patricia Ruramisai; Sibanda, Cathrine (African studies (Johannesburg), 2025)
This paper explores the discursive construction of climate change in the narratives of the Doma, an indigenous community in the Zambezi Valley in Zimbabwe. It adopts a qualitative methodology that involves in-depth interviews with members of the Doma community. The data were analysed thematically, and the focus is on how the narratives of the Doma construct meaning around the causes and solutions to climate change and how cultural and historical contexts and entanglements shape these meanings. The findings reveal that the Doma have a rich and complex understanding of climate change, both in terms of its causes and response, based on their intimate relationship with the natural environment. Their narratives construct meanings around the causes and solutions to climate change that differ from the dominant scientific and prevailing political discourses. The meanings in such narratives emphasise the interconnectedness of social and ecological systems and the agency of non-human actors in shaping the environment. Overall, the paper concludes that it is important to include indigenous knowledge systems in the discourse around climate change, and there is a need for a more holistic and inclusive understanding of the global challenge of climate change.